2022
DOI: 10.3389/fneur.2022.881190
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Macular Retinal Thickness in Patients With Pterygium

Abstract: PurposeTo explore alterations in macular retinal thickness (RT) and analyze correlation between macular RT and pterygium area, length in pterygium patients.MethodsTotally 13 patients with pterygium (left eye) and 13 healthy controls (left eye) were recruited. OCTA was applied to scan each eye to generate three-dimensional images. Based on the Early Treatment Diabetic Retinopathy Study (ETDRS) method, each image was divided into nine subregions for the ETDRS: central (C); inner superior (IS); outer superior (OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Moreover, multiple studies have revealed that pterygia and macular degeneration (MD) share a common affected population; namely, individuals exposed to solar radiation (SR) [6]. Recent investigations have demonstrated a reduction in macular retinal thickness and retinal microvasculature densities in patients with pterygia [7,8]. Until now, the alterations that occur in the macula microvascular of pterygium patients as well as the underlying mechanisms of development have remained to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, multiple studies have revealed that pterygia and macular degeneration (MD) share a common affected population; namely, individuals exposed to solar radiation (SR) [6]. Recent investigations have demonstrated a reduction in macular retinal thickness and retinal microvasculature densities in patients with pterygia [7,8]. Until now, the alterations that occur in the macula microvascular of pterygium patients as well as the underlying mechanisms of development have remained to be elucidated.…”
Section: Introductionmentioning
confidence: 99%